Perlindungan Hukum Terhadap Indikasi Geografis Atas Klaim Wilayah Rambutan Parakan Tanpa Izin Berdasarkan Undang-Undang Nomor 20 Tahun 2016 Tentang Merek dan Indikasi Geografis - Dini Cahyati; Anne Gunawati; Rully Syahrul Mucharom (Gapenas Publisher, 2026)
Indonesia is a country rich in natural resources because Indonesian land has various natural products with their own unique characteristics. The uniqueness of natural resources, both plant and biological, so that from this potential provides various products such as agriculture, plantations, cultivation, crafts, and forestry. Having the characteristic of a geographical indication is located. Geographical Indication is a sign that indicates the area of ??origin of a good and/or product which due to geographical environmental factors including natural factors, human factors or a combination of both factors gives a certain reputation, quality, and characteristics to the goods and/or products produced. One of the potential products of geographical indication is the Parakan rambutan product typical of Tangerang Regency. Problems arise when there is misuse of the Parakan rambutan area belonging to Tangerang Regency which has been certified as a geographical indication by another party, this is detrimental to the economic rights of the owner of the geographical indication. This study aims to analyze the protection of the geographical indication of parakan rambutan based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications and the legal consequences of violators of the use of Geographical Indications of parakan rambutan without permission based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The method used is normative juridical. Data collection techniques are carried out through library studies and field studies. Data analysis uses qualitative analysis. The results of the study indicate that the protection of geographical indications for the use of the parakan rambutan area is legally protected because it has been certified in accordance with the geographical indication document and the consequences of the issue are detrimental to the reputation, quality and characteristics and violate the economic rights of the geographical indication owner. The geographical indication owner can file a civil or criminal lawsuit. Suggestions given, it is necessary to improve the label on the packaging of Geographical Indication products and supervision from the government, geographical indication owners or other communities.